1973
DOI: 10.1017/s0043174500032008
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter Effect on Activity of Acetanilides, CDAA, and Atrazine

Abstract: Field and greenhouse studies were conducted to determine the influence of soil organic matter on herbicidal activity using four Pocomoke soils with organic matter contents of 4.8, 7.0, 11.9, and 17.0%. In field experiments, control of giant green foxtail [Setaria viridisvar.major(Gaud.) Posp.] was greater than 75% from all treatments of 2-chloro-2′,6′-diethyl-N-(methoxymethyl) acetanilide (alachlor), 2-chloro-N-isopropylacetanilide (propachlor), andN,N-diallyl-2-chloroacetamide (CDAA) with no statistical diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
3
15
0
2
Order By: Relevance
“…The activity of both formulations of either herbicide was reduced with increasing organic matter content and this could be attributed mainly to adsorption differences caused by the increase of organic matter content. Similar results were reported by Parochetti (1973) and Peter & Weber (1985). The reduced release of ME‐alachlor in mixtures with the highest organic matter content owing to reduced microbial activity from the pH reduction (7.2 and 6.0 in 0 and 8% organic matter content respectively) may account for the activity differences between ME‐ and EC‐alachlor.…”
Section: Resultssupporting
confidence: 84%
“…The activity of both formulations of either herbicide was reduced with increasing organic matter content and this could be attributed mainly to adsorption differences caused by the increase of organic matter content. Similar results were reported by Parochetti (1973) and Peter & Weber (1985). The reduced release of ME‐alachlor in mixtures with the highest organic matter content owing to reduced microbial activity from the pH reduction (7.2 and 6.0 in 0 and 8% organic matter content respectively) may account for the activity differences between ME‐ and EC‐alachlor.…”
Section: Resultssupporting
confidence: 84%
“…For example, Parochetti (1973) found that atrazine was much more strongly affected by organic matter than were CDAA and alachlor. Peek and Appleby (1989) found no correlation between bioactivity of metribuzin or its thio analog and clay content, cation exchange capacity (CEC), or organic matter in 5 Oregon soils.…”
Section: Introductionmentioning
confidence: 99%
“…showing that the herbicide dosage necessary to obtain a determined level of weed control is related to the soil capacity for herbicide adsorption and that the differences become accentuated when the amount of soil organic matter increases. Parochetti (1973) observed a positive correlation between the amount of organic matter and the alachlor dosage required to control 50% of the weed Seiaria faberi (Herrm), whereas Peter and Weber (1985) observed that the alaehlor and metolachlor dosage necessary to control 80% ofthe weeds {Amaranthu.s relojie.xus L., Ambrosia artemiisifotia L.. and Echlnochloa crusgalU L.) increased with an increase in soil organic matter.…”
Section: Results and Discusionmentioning
confidence: 99%